Palaeomagnetic indication for India–Asia collision at 12°N and maximum 810 km Greater India extent in the western suture zone. Issue 2 (4th January 2022) - Dannemann, Sven; Appel, Erwin; Rösler, Wolfgang; Neumann, Udo; Liebke, Ursina; Nag, Debarati
SUMMARY: Knowing the pre-collisional extent of the northern Indian Plate margin ('Greater India') is vital to understanding the tectonic evolution of the India–Asia collision and the formation of the Himalayan–Tibetan orogen. However, suitable geological units for palaeomagnetic investigations along the Himalayan belt are limited, which makes it difficult to reconstruct Greater India during the pre-collisional period in Late Cretaceous to Palaeogene. Often the palaeomagnetic results from the Zongpu Formation at Gamba in southern Tibet (∼88.5°E) were used for estimates of Greater India, but their validity was recently questioned. As a contribution to closing the data gap, we performed a palaeomagnetic study of the Palaeocene/Lower Eocene Dibling limestone (DL) in the western Tethyan Himalaya of Zanskar (34.0°N/76.6°E). The results from 27 sites revealed a well grouping ( k = 71.7) syntectonic magnetization with best grouping at 52 per cent unfolding. The remagnetization of the DL was acquired shortly after ∼54 Ma, at the latest at ∼49 Ma, and is probably carried by fine-grained magnetite formed during the early orogenic phase. Assuming proportional tilting of the fold limbs, the corresponding palaeolatitude of 11.8 ± 2.4°N suggests a maximum Greater India extent of 810 ± 420 km and a first continental contact with the southern Eurasian margin at ∼12°N in the western part of the suture zone. The tectonostratigraphic equivalence of the DL with the Zongpu Formation at Gamba and a great similarity in their magnetic properties supports a secondary origin of the Gamba results. Through understanding the mechanism of remagnetization in the DL, an early orogenic remanence acquisition is also indicated for the Zongpu Formation, and thus the Gamba results deserve further credit for Greater India reconstructions. However, we note a large inconsistency of the available Late Cretaceous and Palaeogene palaeolatitude data from the Tethyan Himalaya by up to ∼20°, corresponding to differences of up to ∼2000 km in the size of Greater India. These discrepancies require further palaeomagnetic work in the Tethyan Himalaya, and in particular we recommend comparative studies at same locations and of same units.